THE EFFECT OF THE DRILL TRAINING METHOD ON IMPROVING VOLLEYBALL SMASH ACCURACY AMONG MEMBERS OF THE PHYSICAL EDUCATION STUDENT VOLLEYBALL CLUB AT ABULYATAMA UNIVERSITY - Rawi Juwanda; Husnul Mubaraq; Boihaqi; Aldiansyah Akbar (CV Abid Abadi Jaya, 2026)
This study aimed to examine the effect of the drill training method on improving volleyball smash accuracy among members of the Volleyball Student Activity Unit (UKM) at Abulyatama University. A quantitative approach with a quasi-experimental method was employed using a One Group Pretest–Posttest Design. The study involved all 12 active members of the volleyball club using a total sampling technique. Participants completed a drill-based smash training program consisting of eight training sessions. Volleyball smash accuracy was assessed using the smash accuracy test developed by Nurhasan (2001). Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-samples t-test with IBM SPSS Statistics version 26 at a significance level of 0.05. The findings revealed that the mean smash accuracy score increased from 2.67 ± 1.303 in the pretest to 3.92 ± 0.996 in the posttest. The paired-samples t-test indicated a statistically significant difference between the pretest and posttest scores (p = 0.000 < 0.05). These findings demonstrate that the drill training method effectively improves volleyball smash accuracy. Therefore, drill-based training can be recommended as an effective training strategy for enhancing smash performance among university students and volleyball athletes